Glaucoma - Intraocular Pressure and Aqueous Dynamics 2016
DOI: 10.5772/65972
|View full text |Cite
|
Sign up to set email alerts
|

Managing Intraocular Pressure: Innovation in Glaucoma Management

Abstract: Primary open-angle glaucoma is a progressive ocular neuropathy that if left untreated may lead to blindness. The main risk factor for developing glaucoma is increased intraocular pressure. Intraocular pressure is regulated by the balance of aqueous humour synthesis and secretion into the eye and outflow from the eye; therefore, most therapies for glaucoma seek lowering intraocular pressure to avoid disease progression. There are several types of drugs in the market for the treatment of glaucoma, but there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Flavonoids in Gingko biloba L. may attenuate RGC injuries in glaucoma by suppressing ROS-induced apoptosis [236]. However, a clinical study comparing oral antioxidants, including extracts of Ginkgo biloba and α-tocopherol, for the treatment of glaucoma (NCT01544192) did not show any clear benefits associated with the use of Ginkgo biloba [237]. Coenzyme Q 10 , another flavonoid, has been shown to reduce glutamate excitotoxicity and ROS formation in a mice model of glaucoma, thus preserving RGCs from apoptosis by reducing Bax expression and enhancing Bad protein expression [238].…”
Section: Promising Antioxidants For Glaucoma Treatmentmentioning
confidence: 99%
“…Flavonoids in Gingko biloba L. may attenuate RGC injuries in glaucoma by suppressing ROS-induced apoptosis [236]. However, a clinical study comparing oral antioxidants, including extracts of Ginkgo biloba and α-tocopherol, for the treatment of glaucoma (NCT01544192) did not show any clear benefits associated with the use of Ginkgo biloba [237]. Coenzyme Q 10 , another flavonoid, has been shown to reduce glutamate excitotoxicity and ROS formation in a mice model of glaucoma, thus preserving RGCs from apoptosis by reducing Bax expression and enhancing Bad protein expression [238].…”
Section: Promising Antioxidants For Glaucoma Treatmentmentioning
confidence: 99%
“…PERK activates eukaryotic initiation factor 2α (eIF2α), which downregulates overall protein translation, indirectly protecting the cell from protein misfolding [235]. PERK also upregulates activating transcription factor 4 (ATF-4), which triggers the CCAAT/enhancer-binding protein (C/EBP) homologous protein (CHOP), exerting a proapoptotic function [240]. In this regard, Han et al demonstrated that a sustained activation of ATF-4 and CHOP increases protein synthesis and leads to cell death through oxidative stress and ATP depletion [236].…”
Section: Interplay Between Mitochondrial and Er Stress In Tmcs And Rgcsmentioning
confidence: 99%
“…These interactions suggest that Gingko biloba extracts may reduce RGC damage in glaucoma by inhibiting H 2 O 2 -related apoptosis through pathways involving p53, Bax/Bcl-2, and caspase-3/9 [265]. A dedicated clinical trial evaluated the use of oral antioxidants for glaucoma, comparing extracts of Gingko biloba with α-tocopherol for 3 months (NCT01544192), and completed phase III, reporting no clear clinical benefit for the use of Gingko biloba [240]. Another flavonoid, coenzyme Q 10 , a natural lipophilic compound, has demonstrated in murine glaucoma models its ability to reduce glutamate excitotoxicity and oxidative stress, promoting RGC survival and preventing apoptotic cell death by decreasing Bax expression and increasing the Bcl-2 associated agonist of cell death (Bad) protein expression [266].…”
Section: Therapeutic Perspectives In Glaucoma 421 Therapeutic Potenti...mentioning
confidence: 99%
“…These interactions suggest that Gingko biloba extracts may reduce RGC damage in glaucoma by inhibiting H₂O₂-related apoptosis through pathways involving p53, Bax/Bcl-2, and caspase-3/9 [272]. A dedicated clinical trial evaluated the use of oral antioxidants for glaucoma, comparing extracts of Gingko biloba with α-tocopherol for 3 months (NCT01544192), and completed phase III, reporting no clear clinical benefit for the use of Gingko biloba [273]. Another flavonoid, coenzyme Q₁₀, a natural lipophilic compound, has demonstrated in murine glaucoma models its ability to reduce glutamate excitotoxicity and oxidative stress, promoting RGC survival and preventing apoptotic cell death by decreasing Bax expression and increasing the Bcl-2 associated agonist of cell death (Bad) protein expression [274].…”
Section: Therapeutic Perspectives In Glaucoma 421 Therapeutic Potenti...mentioning
confidence: 99%